Psychometric Properties of the General Health Questionnaire (GHQ-28) in Ecuadorian College Students - Moreta-Herrera, Rodrígo (2021)
Objective: To analyse the internal structure of the 28-item version of the General Health Questionnaire (GHQ-28), as well as its reliability and validity in relation to other variables in a sample of Ecuadorian university students. Method: Instrumental design with confirmatory factor analysis using weighted least square mean and variance adjusted (WLSMV) estimator, reliability and convergence and discrimination validity of the GHQ-28. Sample: 495 students (56.6% women), between 18 to 35 years old (M = 24.1 years; SD = 2.1), from three universities (59.6% public) in Ecuador. Results: The bifactor model of the GHQ-28 test has an adequate fit with χ2 = 357.81; p > .05; df = 322; χ2/df = 1.11; CFI = .991; TLI = .989; SRMR = .059; RMSEA = .015 [.000 – .023]; ωH = .93; ECV = .90; PUC = .78. The GHQ-28 is reliable and in terms of convergent validity, it correlates significantly and negatively with mental health, assessed by MHC-SF, and it is discriminant between risk and non-risk cases. Conclusion: The GHQ-28 bifactor model is replicable in Ecuadorian college students.